Attempt to Silence Genes of the RNAi Pathways of the Root-Knot Nematode, Meloidogyne incognita Results in Diverse Responses Including Increase and No Change in Expression of Some Genes - Iqbal, Sadia; Fosu-Nyarko, John; Jones, Michael G. K. (Frontiers in Plant Science, 2020)
Control of plant-parasitic nematodes via Host-Induced Gene Silencing (HIGS) involves rational selection of genes and detailed assessment of effects of a possible knockdown on the nematode. Some genes by nature, may be very important for the survival of the nematode that down regulation may be resisted. Possible silencing and effects of 20 such genes involved in the RNA interference (RNAi) pathways of Meloidogyne incognita were investigated in this study using long double stranded RNAs (dsRNAs) as triggers. Two of the genes, ego-1 and mes-1 could not be knocked down. Expression of six genes (xpo-1, pash-1, xpo-2, rha-1, ekl-4 and csr-1) were significantly upregulated after RNAi treatment whereas for 12 of the genes, significant knockdown was achieved and with the exception of mes-2 and mes-6, RNAi was accompanied by defective phenotypes in treated nematodes including various degrees of paralysis and abnormal behaviours and movement such as curling, extreme wavy movements, and twitching. These abnormalities resulted in up to 75% reduction in infectivity of a tomato host, the most affected being the J2s previously treated with dsRNA of the gfl-1 gene. For 10 of the genes, effects of silencing in the J2s persisted as the adult females isolated from galls were under-developed, elongated and transparent compared to the normal saccate, white adult females. Following RNAi of ego-1, smg-2, smg-6 and eri-1, reduced expression and/or the immediate visible effects on the J2s were not permanent as the nematodes infected and developed normally in tomato hosts. Equally intriguing was the results of RNAi of the mes-2 gene where the insignificant change in gene expression and behaviour of treated J2s did not mean the nematodes were not affected as they were less effective in infecting host plants. HIGS of drsh-1, mut-7, drh-3, rha-1, pash-1 and vig-1 confirmed that plant-processed dsRNA and/or siRNA can silence the genes and led to reduction in nematode infestation by up to 89%. Our results show that genes may respond to RNAi knockdown differently so an exhaustive assessment of target genes as targets for nematode control via RNAi is imperative.